Analisis Kemampuan Berbahasa Indonesia Pada Anak Usia 4-5 Tahun Melalui Dongeng Ke’ Lesap - Prameswari, Aldila; Pratiwi, Eriqa; Abdul Latif, Muhammad (Nak-Kanak: Journal of Child Research, 2024)
This study aims to analyze the Indonesian language skills of children aged 4-5 years through the story of Ke' Lesap. The research method used is descriptive qualitative. The subjects of this study are children in the 4-5 age group, focusing on their ability to understand and use Indonesian after being exposed to the story. Data collection was conducted through direct observation and interviews with teachers and parents to obtain a comprehensive picture of the children's language development. The results of this study show that children in this age range are already able to use Indonesian well. They demonstrated improvements in vocabulary, sentence structure, and narrative ability after routinely listening to the story of Ke' Lesap. A significant factor contributing to this improvement is the stimulus provided by the storytelling. The story of Ke' Lesap not only captures children's attention but also stimulates their imagination, which in turn encourages them to communicate more actively and use Indonesian in their daily lives. Furthermore, this study found that storytelling is very effective in introducing complex language concepts in a fun and easily understood manner by children. Teachers and parents also reported increased motivation among children to learn and communicate after participating in storytelling activities. Thus, it can be concluded that the story of Ke' Lesap is highly effective in developing the Indonesian language skills of children aged 4-5 years. This study suggests that storytelling methods should be used more frequently in early childhood education programs to enhance language skills and communication abilities. These findings also contribute significantly to the development of more creative and story-based educational curricula for children.